Mali Africa Research in Sustainable Intensification for the Next Generation (Africa RISING) Baseline Evaluation Survey - International Food Policy Research Institute (International Food Policy Research Institute, 2015)
As part of the US government’s Feed the Future initiative that aims to address global hunger and food security issues in sub-Saharan Africa, the US Agency for International Development is supporting three multi-stakeholder agricultural research projects under Africa Research In Sustainable Intensification for the Next Generation (Africa RISING - AR) program. The overall aim of the program is to transform agricultural systems through sustainable intensification projects in Ghana, Ethiopia, Tanzania, Malawi, Mali, and (potentially) Zambia. In West Africa, IITA works with multi-disciplinary R4D partners in selected communities located in Northern Ghana and Southern Mali. More particularly, in Southern Mali the AR-WA project focuses on sorghum-millet-legume-vegetable-livestock systems in the Bougouni, Yanfolila and Koutiala districts, which are situated in the Sikasso region. The Africa RISING partners in Mali include several international institutions: the International Crops Research Institute for the Semi-Arid Tropics (ICRISAT), the International Livestock Research Institute (ILRI), the Asian Vegetable Research and Development Center (AVRDC), the International Center for Research in Agroforestry or World Agroforestry Center (ICRAF); as well as local partners: L’Association Malienne d’Eveil et de Développement Durable (AMEDD), L'Association Malienne pour la Sécurité et la Souveraineté Alimentaires (AMASSA), Mouvement Biologique du Mali (MOBIOM).